Computational insights of alkali metal (Li / Na / K) atom decorated buckled bismuthene for hydrogen storage. (13th August 2021) - Khan, Muhammad Isa; Zaigam, Syeda Masooma; Majid, Abdul; Tahir, Muhammad Bilal
Abstract: The mechanism of hydrogen molecule adsorption on 2D buckled bismuthene (b-Bi) monolayer decorated with alkali metal atoms was studied using density functional theory based first principles calculations. The decorated atoms Li, Na and K exhibited distribution on surface of b-Bi monolayer with increasing binding energy of 2.6 eV, 2.9 eV and 3.6 eV respectively. The adsorption of H2 molecule on the slabs appeared stable which was further improved upon inclusion of van der Waals interactions. The adsorption behaviour of H2 molecules on the decorated slabs is physisorption whereas the slabs were able to bind up to five H2 molecules. The average adsorption energy per H2 molecules are in range of 0.1–0.2 eV which is good for practical applications. The molecular dynamics simulation also confirmed the thermodynamic stabilities of five H2 molecules adsorbed on the decorated slabs. The storage capacity values are found 2.24 wt %, 2.1 wt %, and 2 wt %, for respective cases of Li, Na and K atoms decorated b-Bi. The analysis of the adsorbed cases pointed to electrostatic interaction of Li and H2 molecule. The adsorption energies, binding energies, charge analysis, structural stability, density of states, and hydrogen adsorption percentage specifies that the decorated b-Bi may serve as an efficient hydrogen storage material and could be an effective medium to interact with hydrogen molecules at room temperature. Graphical abstract: Image 1 Highlights: Li, Na and K atoms shown strongest binding with b-Bi with increased binding energy 2.6 eV, 2.9 eV and 3.4 eV respectively. H2 interacted more strongly with Li, Na and K atoms on b-Bi with improved adsorption energies. The value of hydrogen storage capacity of functionalized b-Bi for Li, Na and K atoms are 2.24, 2.1 and 2 wt % respectively. Hydrogen molecules are physisorbed on metal atoms functionalized bismuthene. H2 on AM b-Bi complexes are more stable than H2 b-Bi for effective H2 storage.